DIGITAL TRANSFORMATION IN THE SPORTS INDUSTRY - Tustikbaev, N.A. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
The article is devoted to digital transformation of physical culture and sports in Kazakhstan. Special attention is paid to the conditions of transition to the information society, developed information competences become a key factor for successful work in various fields, including sports.
Keywords: digital transformation; physical education; digital educational resources; the field of physical culture and sports